2018
DOI: 10.1152/ajpregu.00210.2017
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and long-term effects of maternal uterine artery adenoviral VEGF-A165 gene therapy in the growth-restricted guinea pig fetus

Abstract: Uterine artery application of adenoviral vascular endothelial growth factor A (Ad.VEGF-A) gene therapy increases uterine blood flow and fetal growth in experimental animals with fetal growth restriction (FGR). Whether Ad.VEGF-A reduces lifelong cardiovascular disease risk imposed by FGR remains unknown. Here, pregnant guinea pigs fed 70% normal food intake to induce FGR received Ad.VEGF-A (1×10 viral particles, n = 15) or vehicle ( n = 10), delivered to the external surface of the uterine arteries, in midpregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…29 Experiments were performed in normal pregnant sheep, [30][31][32] FGR pregnant sheep, 33,34 and FGR pregnant guinea pigs. 29,35,36 We chose pregnant sheep in which to first assess the effect of maternal gene therapy on uterine blood flow and fetal growth because many aspects of sheep fetal and vascular physiology are similar to the human and because the ovine fetus is similar in size to the human. Moreover, ultrasound quantification of uterine blood flow, fetal growth, and well-being is a validated technique for monitoring normal and FGR sheep pregnancy, and which allows comparison with human FGR.…”
Section: Introductionmentioning
confidence: 99%
“…29 Experiments were performed in normal pregnant sheep, [30][31][32] FGR pregnant sheep, 33,34 and FGR pregnant guinea pigs. 29,35,36 We chose pregnant sheep in which to first assess the effect of maternal gene therapy on uterine blood flow and fetal growth because many aspects of sheep fetal and vascular physiology are similar to the human and because the ovine fetus is similar in size to the human. Moreover, ultrasound quantification of uterine blood flow, fetal growth, and well-being is a validated technique for monitoring normal and FGR sheep pregnancy, and which allows comparison with human FGR.…”
Section: Introductionmentioning
confidence: 99%
“…A potential treatment for FGR is maternal gene therapy which aims to increase the local availability of Vascular Endothelial Growth Factor (VEGF) in the maternal uteroplacental circulation. Preclinical studies have shown that maternal uterine artery administration of adenovirus vectors containing the VEGF gene in pregnancy increases uterine blood flow, angiogenesis and fetal growth [36].…”
Section: Introductionmentioning
confidence: 99%
“…The medical plausibility for maternal VEGF gene therapy is based on the observation that reduced uterine blood flow is a key pathology in placental insufficiency, and that manipulation of VEGF expression can improve uterine blood flow, increase uterine artery relaxation and endothelial nitric oxide synthase production, and increase local angiogenesis . In preclinical animal models we have previously shown that local maternal VEGF gene transfer to the utero–placental circulation using adenovirus vectors increases uterine blood flow, attenuates constriction of the uterine arteries and increases angiogenesis; these changes result in improved growth of severely growth restricted fetuses …”
Section: Discussionmentioning
confidence: 99%
“…56,57 In preclinical animal models we have previously shown that local maternal VEGF gene transfer to the utero-placental circulation using adenovirus vectors increases uterine blood flow, attenuates constriction of the uterine arteries and increases angiogenesis; 58 these changes result in improved growth of severely growth restricted fetuses. [59][60][61][62]…”
Section: Additional Requirements For Ema Orphan Drug Designationmentioning
confidence: 99%